2015
DOI: 10.1016/j.neuro.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles at sublethal concentrations disrupt cytoskeleton and neurite dynamics in cultured adult neural stem cells

Abstract: Silver nanoparticles (AgNPs) have potent antimicrobial properties at concentrations far below those that cause cytotoxic and genotoxic effects in eukaryotic cells. This property has resulted in the widespread use of AgNPs in consumer products, leading to environmental exposures at sub-lethal levels through ingestion and inhalation. Although the toxicity of AgNPs has been well characterized, effects of environmentally relevant exposures have not been extensively investigated in spite of studies that suggest acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…Nanoparticles could impact on cytoskeletal dynamics and organization directly, from within the cytoplasm, or indirectly through interactions with extracellular matrix components or transmembrane receptors ( e.g ., integrins). Interestingly, a recent study has shown that sublethal concentrations of silver nanoparticles disrupted cytoskeletal organization and neurite extension in cultured adult neural stem cells derived from rat brain, likely through a direct effect on actin dynamics 64 . In contrast, our results suggested an effect of nanoceria at the transcriptional level in differentiating neural stem cells.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoparticles could impact on cytoskeletal dynamics and organization directly, from within the cytoplasm, or indirectly through interactions with extracellular matrix components or transmembrane receptors ( e.g ., integrins). Interestingly, a recent study has shown that sublethal concentrations of silver nanoparticles disrupted cytoskeletal organization and neurite extension in cultured adult neural stem cells derived from rat brain, likely through a direct effect on actin dynamics 64 . In contrast, our results suggested an effect of nanoceria at the transcriptional level in differentiating neural stem cells.…”
Section: Resultsmentioning
confidence: 99%
“…Past studies with varying length to AgNP exposure in rodents and fish suggest that these chemicals can result in several neuropathological changes, such as edema formation, neuronal degradation and apoptosis, synaptic degeneration, tight junction disruptions, increase in reactive oxygen species (ROS), disturb brain antioxidant system, amyloid-β (Aβ) plagues, and astrocyte swelling 15-18, 20, 22, 23, 26-31, 49-52 . AgNPs may also disrupt the cytoskeleton architecture in neuronal cells 53 . Several transcripts are altered in neurons of mice or rats exposed to AgNPs, such as Psen1, Psen2, Trex1, Irf7, RasGrf1, Bcl2, Th, Maoa, Cdh1, Cldn1, and Il4 16,54,55 .…”
Section: Discussionmentioning
confidence: 99%
“…Schematically, the presence of nanoparticles in astrocytes may participate in the induction of reactive gliosis, while in the case of nanoparticle accumulation in neurons, there may be changes in neuronal metabolism, functions, or even viability. Finally, the sub-cellular scale also has its own importance, as suggested by a study reporting the loss of β-tubulin and actin filamentin cultured neurons exposed to 20 nm silver nanoparticles (Xu et al, 2013a); this observation was reproduced at sublethal concentrations of silver nanoparticles which disrupt also actin dynamics in SVZ-NSCs (Cooper and Spitzer, 2015). Among the possible expected effects, impacts on cell morphology, function, and viability are critical for the highly vulnerable nerve cells, when compared to other cell types.…”
Section: Possible Effects On the Nervous Systemmentioning
confidence: 90%